Active vibration control systems for driver's seat of earth-moving vehicles - BALLO, I. (Archives of Acoustics, 1993)
In the article a survey of the activity of the Institute of Materials and Machine Mechanics of the Slovak Academy of Sciences in the field of research of active vibration control systems (AVIS) is given. The contribution starts with some remarks on the vibration control properties of common passive systems. In the next part the possibilities of combination of passive and active vibration control systems (VCS) are discussed. The next topic are the results of theoretical and experimental research of electro-hydraulic and electro-pneumatic acitve VCS for driver seats in earth-moving machines. The last part of the paper deals with the problem of power consumption of the AVIS.